Phylogeny and Classification of Yersinia pestis Through the Lens of Strains From the Plague Foci of Commonwealth of Independent States - Kutyrev, Vladimir V.; Eroshenko, Galina A.; Motin, Vladimir L.; Nosov, Nikita Y.; Krasnov, Jaroslav M.; Kukleva, Lyubov M.; Nikiforov, Konstantin A.; Al’khova, Zhanna V.; Oglodin, Eugene G.; Guseva, Natalia P. (Frontiers in Microbiology, 2018)
The established phylogeny of the etiological agent of plague, Yersinia pestis, is not perfect, as it does not take into account the strains from numerous natural foci of Commonwealth of Independent States (CIS). We have carried out PCR and SNP typing of 359 strains and whole genome sequencing of 51 strains from these plague foci and determined the phylogenetic diversity of the strains circulating here. They belong to 0.ANT3, 0.ANT5, 2.ANT3, 4.ANT branches of antique biovar, 2.MED0, 2. MED1 branches of medieval biovar and to 0.PE2, 0.PE4a. 0.PE4h, 0.PE4t branches. Based on the studies of 178 strains from 23 plague foci of CIS countries, it was determined that the population structure of 2.MED strains is subdivided into Caucasian-Caspian and Central Asian-Chinese branches. In Central-Caucasian high-mountain plague foci in the Russian Federation (RF) the most deeply diverged branch of medieval biovar, 2.MED0, has been found. With the data obtained, the current population structure of Y. pestis species has been refined. New subspecies classification is developed, comprising seven subspecies: pestis, caucasica (0.PE2), angolica (0.PE3), central asiatica (0.PE4), tibetica (0.PE7), ulegeica (0.PE5) and qinghaica (0.PE10). Key words Plague agent, phylogenetic diversity, subspecies classification, PCR and SNP typing, whole genome sequencing